PENINGKATAN KOMPETENSI PROFESIONAL GURU BIOLOGI MADRASAH ALIYAH MELALUI PEMBELAJARAN JARAK JAUH - Himawati Hanurani (Tatar Pasundan: Jurnal Diklat Keagamaan, 2019)
This study aims to determine increasing mastery of the concept of biology teacher Madrasah Aliyah in West Java Province through distance learning. In this research, teachers are given distance training based on e-learning. The research type used is pre-experimental with one group of pre-test and post-test design. The design procedure of this research is to perform the 1st measurement on the subject (pretest) on the ability of mastery of the concept of biology aspects of virus and prokaryotes then subjects are given treatment for a certain period (exposure) through distance training. The 2nd measurement (post-test) is performed after the treatment is given. This research based on distance learning Theory.  The result of measurement of pre-test compared with result of post-test measurement, t- test statistic. The result of t-test shows there are significant difference of result of concept test of virus and prokaryotes between before and after doing Distance Learning. From the results of the study it can be concluded that there is an increase in test score of concept master before following distance training and after following distance training with medium N-Gain. Keywords: Teachers’ Competence; Distance Traning; Biology Teacher